Etymology of Risk, Vulnerability, Exposure and Resilience in Latin, Greek and Hebrew - Markus, Patrick C. G. F. (2026)
This paper addresses the etymology of the categories of risk, vulnerability, exposure and resilience, notions commonly used in relation to the study of disasters. The etymological references in Latin, Greek and Hebrew are examined. The main social imageries associated with the original meanings are briefly laid out. This paper concludes that all four words, as we know them today, have their origins in Latin, as opposed to Greek or Hebrew.